Sorafenib after arterial chemoembolization in child-pugh A and B cirrhotic patients with intermediate hepatocellular carcinoma: a retrospective analysis - Romeiro, Fernando Gomes [UNESP]; Sigahi, Luciana Yumi Odani [UNESP]; Alvarez, Matheus [UNESP]; Yamashiro, Fabio da Silva [UNESP]; Carvalho, Fábio Cardoso de [UNESP]; Pelafsky, Leonardo [UNESP]; Lima, Talles Bazeia [UNESP]; Franzoni, Letícia de Campos [UNESP]; Miranda, José Ricardo de Arruda [UNESP]; Silva, Giovanni Faria [UNESP] (Scientific Research Publishing, 2015)
Introduction: Hepatocellular carcinoma (HCC) is a leading cause of mortality among cirrhotic patients, and current guidelines recommend single-treatment modalities according to patient and liver disease classifications. New studies have shown promising results from combining locoregional and systemic treatments, but most of them were limited to Child-Pugh A patients due to toxicity concerns. Aim: The objective of this study was to analyze survival rates of Child-Pugh A and B patients with intermediate HCC tumors treated with transarterial chemoembolization (TACE) followed by full-dose sorafenib usage. Material and methods: a retrospective analysis of 37 cirrhotic patients (Child-Pugh A and B rates = 23/14) treated with TACE and TACE followed by sorafenib usage (17 and 20 patients, respectively). Results: The mean survival was 379 days in the combined treatment group and 151 days in the single-treatment group (p = 0.007). There were no differences in survival according to the Child-Pugh classification. Conclusions: sorafenib after TACE can be an option for selected cirrhotic patients with intermediate HCC tumors if this combined approach is cautiously performed on an individualized schedule. Our results suggest that the Child-Pugh classification should not be a limitation to this combined treatment.
Keywords: Hepatocellular carcinoma; Cirrhosis; Arterial chemoembolization; Sorafenib